2005
DOI: 10.1097/00006982-200509000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Retinal Indocyanine Green Dye by Autologous Serum Irrigation in Macular Hole Surgery

Abstract: Autologous serum irrigated in the vitreous cavity just before completion of macular hole surgery can help remove ICG dye used in surgery. The application was simple and safe and significantly shortened the period of residual retinal ICG staining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…6,7 It has been reported that ICG can remain in the eye for several months, and infrared hyperfluorescence from ICG may persist for up to 36 months after ICG-assisted ILM peeling. 12,25 Consequently, the persistence of ICG may, in turn, cause prolonged adverse effects by promoting phototoxicity. 25 Possible solutions to minimize the adverse effects of ICG include brief intravitreal application of a small amount of ICG at a low concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,7 It has been reported that ICG can remain in the eye for several months, and infrared hyperfluorescence from ICG may persist for up to 36 months after ICG-assisted ILM peeling. 12,25 Consequently, the persistence of ICG may, in turn, cause prolonged adverse effects by promoting phototoxicity. 25 Possible solutions to minimize the adverse effects of ICG include brief intravitreal application of a small amount of ICG at a low concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al also reported that autologous serum irrigation before completion of macular hole surgery could help remove residual ICG dye and reduce the persistence of dye, owning to ICG's high affinity and quick binding to lipoprotein in serum. 12 In our study, we sought to evaluate if intraoperative autologous serum could affect the anatomic and functional outcomes of ICG-assisted macular hole surgery. At the baseline, there was no significant difference between vitrectomy with serum and without serum groups in demographic characteristics, such as the percentage of females, mean age, mean refractive errors, mean axial length, mean preoperative VA, lens status, staging of macular hole, duration of symptoms, and follow-up time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-El suero autólogo ha sido también utilizado en clínica para la aplicación sobre puntos de fuga en ampollas de filtración (61), en el tratamiento de agujeros maculares de espesor completo, ya sea aplicado sobre el agujero macular o bien usado en el suero de irrigación para limpiar el verde de indocianina usado para visualizar la membrana limitante interna en la cirugía de agujero macular (62,63), desgarros retinianos (64), en asociación con concentrados de plaquetas se ha utilizado en modelos experimentales de cicatrización retiniana (65). -Nosotros estamos empleando suero autólogo en el manejo de la queratopatía cálcica como terapia de apoyo a los quelantes del calcio.…”
Section: Indicacionesunclassified